PEMBELAJARAN MENGGUNAKAN MULTIMEDIA INTERAKTIF BERORIENTASI PADA MATERI ALIRAN ENERGI UNTUK MENINGKATKAN LITERASI SAINS SISWA - Rendy Hendrian Yudhistira; Dhita Ayu Permata Sari; Wahono Widodo (PENSA: E-JURNAL PENDIDIKAN SAINS, 2022)
This study aimed to describe the effect of interactive multimedia in energy flow topics to improve students scientific literacy. The study was quantitative research with one group pretest-posttest design. The subjects were 29 students of class VII-F SMPN 1 Bojonegoro. The instrument of this study were used observation sheets of learning implementation, student activities, student response questionnaires, and scientific literacy tests (pretest and posttest). The data were collected by observation, test, and questionnaire methods. The results of this study showed that there was an improvement of the students scientific literacy by using interactive multimedia in energy flow topics. The students scientific literacy was improved from pretest to posttest with an average of N-Gain score in medium categories. The improvement of students scientific literacy was supported by well-implemented interactive multimedia’s learning, so that it obtained a positive response from students and they did the scientific literacy activities well. So, it can be suggested that interactive multimedia can be applied to other topics.